Processes involved in the design of a segmented rubber tracked vehicle for Sepang peat terrain in Malaysia - Rahman, Mohammed Ataur; Yahya, Azmi; Bardaie, Mohd. Zohadie; Wan Ismail, Wan Ishak (Inderscience Enterprises Ltd., 2005)
This paper describes a framework for designing a new segmented rubber track vehicle for low bearing capacity Sepang peat terrain in Malaysia. Based on a given set of vehicle dimensions and terrain-track system constants, a simulation technique is then used to optimise the design parameters of the vehicle by establishing mathematical models for the track-peat terrain mechanism. The simulation results showed that the nominal ground pressure of the vehicle is 23.5% lower than the bearing capacity of the peat terrain. The location of the centre of gravity of the vehicle at 300mm rearward from the mid-point of the track ground contact length ensures a maximum sinkage of 90 mm, a minimum motion resistance of 12% and a maximum tractive efficiency of 74% during traversing at 10 km/hr on the peat terrain. Finally, the vehicle components have been designed by using 3D-CAD drawing software package.